2019
DOI: 10.1080/13657305.2019.1641570
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis of aquaculture expansion in Arctic Norway

Abstract: According to governmental plans, Norway faces huge expansions in the production of farmed Atlantic salmon. However, it is municipalities that designate coastal areas to aquaculture activities and their motivation depends on net benefits at municipal level from such use. Yet, there is little empirical evidence on costs and benefits of using coastal areas to aquaculture activities. We set up a cost-benefit analysis of salmon farming as seen from a municipal perspective. On the benefit side we count consumer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…2017), others think they can be useful when carefully applied (Knowler 2008). One example of such a trade‐off analysis is Aanesen and Mikkelsen (2020), where there is a cost–benefit analysis of aquaculture expansions in a region, comparing direct and indirect economic impacts with the population’s willingness to pay to get/avoid the expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017), others think they can be useful when carefully applied (Knowler 2008). One example of such a trade‐off analysis is Aanesen and Mikkelsen (2020), where there is a cost–benefit analysis of aquaculture expansions in a region, comparing direct and indirect economic impacts with the population’s willingness to pay to get/avoid the expansion.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors point at controversies and challenges in the application of non-market valuation approaches (Plieninger et al 2013, Bas Vent ın et al 2015, Hanley et al 2015, Pascual et al 2017, others think they can be useful when carefully applied (Knowler 2008). One example of such a tradeoff analysis is Aanesen and Mikkelsen (2020), where there is a cost-benefit analysis of aquaculture expansions in a region, comparing direct and indirect economic impacts with the population's willingness to pay to get/avoid the expansion.…”
Section: Priority Areas For More Economic Datamentioning
confidence: 99%
“…This study employed technical efficiency and profitability as competitiveness proxies to compare agribusiness and non-agribusiness competitivity, following [32,33,[45][46][47][48][49]. Regarding the technical efficiency analysis, we implemented a Data Envelopment Analysis (DEA), while the profitability analysis was based on two indicators, including the cost-benefit ratio and the net monthly revenue.…”
Section: Empirical Approachmentioning
confidence: 99%
“…Given the foregoing, agribusiness will be less attractive to youth if it does not enable them to earn sufficient income as with comparable activities outside agribusiness, such as stores and magazines, hairdressers, restaurants and bistros, pharmacies, and sewing workshops [32][33][34]. Nevertheless, to our knowledge, the existing empirical literature is sparse when it comes to comparing agribusiness and non-agribusiness enterprises and ensuring that agribusiness is more competitive than non-agribusiness enterprises [15,32,33]. A recent study [22] showed that in addition to the success of youth engagement interventions in agribusiness, there is a lack of evidence on what works.…”
Section: Introductionmentioning
confidence: 99%
“…While climate change may have direct effects increasing the vulnerability of some species, it can also trigger the relocation of salmon farms, breeding sites and foraging areas. As salmon farming expands to higher latitudes in both hemispheres, 134,192 interactions with pinnipeds are expected to increase substantially and will probably affect new species, populations and communities in the years to come. The outcomes of such interactions will likely be modulated by the particularities of these new ecosystems, species and populations and the poorly assessed effects of climate change on both farmed salmonids and pinnipeds worldwide.…”
Section: Main Knowledge Gapsmentioning
confidence: 99%